PREVALENCE OF ANEMIA IN PATIENTS WITH MISSED ABORTION - Ana Kocevska; Kristina Skeparovska; Jasmina Chelebieva; Shenol Tahir; Bekim Dika; Iskra Martinovska; Arben Shurlani; Gajur Limani (Македонско лекарско друштво = Macedonian medical association, 2025)
Introduction: Miscarriage (abortion), 85% of which may happen during the first trimester, is one of the most common adverse pregnancy outcomes. Almost half of miscarriages are a consequence of chromosomal abnormalities. The risk factors include advanced maternal age, comorbidities (obesity, diabetes, hypertension), previous miscarriages, smoking and inappropriate nutritional status. Anaemia is the most prominent haematological abnormality during gestation and it is a global health problem affecting nearly half of all pregnant women. Anaemia has been linked to a higher risk of adverse outcomes, including maternal mortality, stillbirth, preterm births, small-for-gestational-age (SGA). World Health Organization has defined anaemia in pregnancy as the haemoglobin (Hgb) concentration of less than 110g/L. The primary cause of anemia during pregnancy is iron deficiency secondary to chronic inadequate dietary intake and menstruation, heightened by the physiologic demands of the fetus and maternal blood volume expansion during pregnancy. The aim of our study was to determine the prevalence of anemia in women with missed abortion in the first trimester of pregnancy, who are not bleeding. Material and methods: In 80 patients with missed abortion in the first trimester of pregnancy, we determined the level of Hgb in capillary blood. Results: In 31 women (38,8%), we detected anemia (the level of Hgb below 110g/L), and 7 of them (8,8% of the total number of women) had a severe anemia with Hgb levels below 90 g/L. As pregnancy progresses, we expect this prevalence to increase. Conclusion: We want to emphasize that a large percentage of women are anemic even preconceptually and early in pregnancy, so if it is not detected and treated, the severity of anemia worsens as the pregnancy progresses.
Keywords: anemia; missed miscarriage; hemoglobin; first trimester of pregnancy